Pengaruh Kebiasaan Jama’ah Tabligh terhadap Persepsi Masyarakat di Paye Munje, Aceh Tenggara - Badrianto Badrianto; Rantoni Rantoni; Nur Aisyah; M. Safri Abbas; Muhammad Abdul Aziz; Umi Kasum; Ros Dewi Hasibuan (Mathematics Education Study Program, 2025)
The aim will be to discuss how the tabligh congregation is very developed in Islamic teachings and also according to the perception of society, currently, whether they do not understand Islamic teachings, and lack of awareness, cleanliness in various places, the tabligh congregation, even the tabligh congregation makes it very easy for them to carry out their activities. communication with the community around today, but the tabligh congregation carries out various activities in religion which are very positive towards their activities, they are still carrying out these activities. The method in this research is qualitative and also descriptive, so that the deeper meaning of the research data can be understood, while the data collection techniques used are observation, interviews and documentation studies, after which it can be processed so that the data can be obtained in research and can be interpreted. The results of this research show that the public's view of the tabligh congregation and the values ​​in the tabligh congregation's habits are both within society and outside the norm.